Ghrelin, MicroRNAs, and Critical Limb Ischemia: Hungering for a Novel Treatment Option - Neale, Joshua P. H.; Pearson, James T.; Katare, Rajesh; Schwenke, Daryl O. (Frontiers in Endocrinology, 2017)
Critical limb ischaemia (CLI) is the most severe manifestation of peripheral artery disease. It is characterised by chronic pain at rest, skin ulcerations, and gangrene tissue loss. CLI is a highly morbid condition, resulting in a severely diminished quality of life and a significant risk of mortality. The primary goal of therapy for CLI is to restore blood flow to the affected limb, which is only possible by surgery, but is inadvisable in up to 50% of patients. This subset of patients who are not candidates for revascularisation are referred to as ‘no-option’ patients, and are the focus of investigation for novel therapeutic strategies. Angiogenesis, arteriogenesis and vasculogenesis are the processes whereby new blood vessel networks form from the pre-existing vasculature and primordial cells respectively. In therapeutic angiogenesis, exogenous stimulants are administered to promote angiogenesis and augment limb perfusion, offering a potential treatment option for ‘no option’ patients. However, to date, very few clinical trials of therapeutic angiogenesis in patients with CLI have reported clinically significant results, and it remains a major challenge. Ghrelin, a 28-amino acid peptide, is emerging as a potential novel therapeutic for CLI. In pre-clinical models, exogenous ghrelin has been shown to induce therapeutic angiogenesis, promote muscle regeneration, and reduce oxidative stress via the modulation of microRNAs (miRs). miRs are endogenous, small, non-coding ribonucleic acids of ~20-22 nucleotides which regulate gene expression at the post-transcriptional level by either translational inhibition or by messenger ribonucleic acid cleavage. This review focuses on the mounting evidence for the use of ghrelin as a novel therapeutic for CLI, and highlights the miRs which orchestrate these physiological events.